Legal Uncertainty of Land Owners in the Implementation of Land Exchange for Elementary School Construction (Case Study of Decision Number: 241/PDT/2015/PT.SMG jo. 74/Pdt.G/2014/PN.Jpa) (Indonesian Journal of Agrarian Law, 2026)
This study examines the legal uncertainty of land owners in exchanging land for the construction of elementary schools by highlighting the administrative and legal aspects. This study uses a legal approach.empirical juridical which combines normative analysis of statutory regulations withwith empirical data obtained through field observations, in-depth interviews with the land swap subjects, the Head of Karanggondang Village and the ATR/BPN of Jepara Regency, as well as analysis of related documents. The results of the study indicate that the implementation of the land swap in this incident was not carried out in accordance with applicable legal procedures because the replacement land promised to the original owner was never actually provided. In addition, there was a transfer of land rights through a land ownership certificate in the name of the village head which created legal uncertainty and harmed the heirs of the land owner. These conditions indicate maladministration and abuse of authority in the land acquisition process for the public interest. Thus, legal certainty in land swaps can only be achieved through transparent administrative procedures, the fulfillment of compensation rights appropriately, and a dispute resolution mechanism that can provide effective legal protection to land owners.